The relationship between hemoglobin and triglycerides in moyamoya disease: A cross-sectional study - Su, Yu; Li, Genhua; Zhao, Huihui; Feng, Song; Lu, Yan; Liu, Jilan; Chen, Chao; Jin, Feng (Frontiers in Neurology, 2022)
Abstract Hemoglobin (Hb) and lipid metabolism are critical in the pathophysiology of moyamoya disease (MMD), and Hb and triglycerides (TGs) both play roles in the development of cerebrovascular illness. However, there is little evidence of a link between Hb and TGs in patients with MMD. This study aimed to determine the association between Hb and TGs in patients who had recently been diagnosed with MMD. From March 2013 to December 2018, 337 patients clinically diagnosed with MMD were admitted to our hospital. Among these, 235 were selected for analysis in this retrospective, cross-sectional study. Each patient's clinical features were documented. For analysis, we used univariate analysis, smoothed-curve fitting, and multivariable, piecewise linear regression. Overall, the mean±standard deviation patient age was 48.14 ± 11.24 years, 44.68% were men, and the mean Hb concentration was 135.72 ± 18.99 g/L. After controlling for relevant confounders, smoothed-curve fitting revealed a nonlinear association between the Hb and TG concentrations (P=0.0448). When the Hb concentration was below 141 g/L, multivariate piecewise linear regression analysis revealed a significant association between the Hb and TG concentrations (β: 0.01, 95% confidence interval [CI]: 0.00, 0.01; P=0.0182), although the association disappeared above this threshold (β: -0.00, 95% CI: -0.01, 0.01; P=0.4429). In individuals newly diagnosed with MMD, there is a significant correlation between Hb and TGs, which may be connected to MMD pathogenesis.